Bringing Visual Inference to the Classroom. Issue 2 (6th August 2021) - Loy, Adam
Abstract: In the classroom, we traditionally visualize inferential concepts using static graphics or interactive apps. For example, there is a long history of using apps to visualize sampling distributions. The lineup protocol for visual inference is a recent development in statistical graphics that has created an opportunity to build student understanding. Lineups are created by embedding plots of observed data into a field of null (noise) plots. This arrangement facilitates comparison and helps build student intuition about the difference between signal and noise. Lineups can be used to visualize randomization/permutation tests, diagnose models, and even conduct valid inference when distributional assumptions break down. This article provides an overview of how the lineup protocol for visual inference can be used to build understanding of key statistical topics throughout the statistics curriculum. Supplementary materials for this article are available online.